Gentrification as space domestication. The High Line Art case. Issue 4 (21st April 2019) - Sacco, Pier Luigi; Tartari, Maria; Ferilli, Guido; Tavano Blessi, Giorgio
ABSTRACT: In this paper, we critically examine the role of artistic locational choices and practices in the context of gentrification processes in urban renewal contexts. We characterize gentrification as a form of domestication of space, and explore the extent to which artistic choices and practices relate to such process with reference to the deontological dilemma of legitimization within the art system vs. responsible empowerment of vulnerable local constituencies. We illustrate our argument with an analysis of the High Line Art project, and show how this can be considered as a textbook example of art-driven space domestication leading to brutal forms of gentrification. We comment on the threat that this provides to the social credibility of artistic practices as an agency of responsible social change.